Scattering of Plane Waves From an Infinite Dielectric Periodic Surface. Issue 8 (17th August 2019) - Wei, Yinyu; Wu, Zhensen; Li, Haiying; Qu, Tan
Abstract: In this paper, the scattering characteristics an infinite dielectric periodic surface are investigated in detail. The Fourier expression of scattering field of the periodic surface is obtained by using the Rayleigh hypothesis and the Floquet theorem. Using the extended boundary condition method and the T‐matrix method, the scattering amplitude factor is solved, and the correctness of the algorithm is verified by use of the law of energy conservation. The scattering cross section of the periodic surface in the infinitely long region is derived by improving the formula of the finite one as its length is increased. Furthermore, the effects of the incident wave parameters and geometric structure parameters on the scattering of the periodic surface are analyzed and discussed. The results show that the period and amplitude of the surface corrugations determine the number of scattering intensity peaks, and influence the scattering intensity distribution with permittivity significantly. Key Points: By use of extended boundary condition method (EBCM) and T‐matrix method, the scattering amplitude factor is solved The scattering cross section of the infinite periodic surface is derived by extending the length of the finite periodic surface The scattering characteristics of dielectric periodic surfaces with several important parameters (such as period, amplitude, and incident angle) are investigated